Advanced Nanomaterials in Multimodal Imaging: Design, Functionalization, and Biomedical Applications. (20th June 2010) - Liu, Zhe; Kiessling, Fabian; Gätjens, Jessica
Abstract : The biomedical applications of nanoparticles in molecular imaging, drug delivery, and therapy give rise to the term "nanomedicine" and have led to ever-growing developments in the past decades. New generation of imaging probes (or contrast agents) and state of the art of various strategies for efficient multimodal molecular imaging have drawn much attention and led to successful preclinical uses. In this context, we intend to elucidate the fundamentals and review recent advances as well as to provide an outlook perspective in these fields.